2021
DOI: 10.1177/02654075211002663
|View full text |Cite
|
Sign up to set email alerts
|

Resolving the cultural loneliness paradox of choice: The role of cultural norms about individual choice regarding relationships in explaining loneliness in four European countries

Abstract: Do cultural norms that allow individuals to choose their social relationships put them at risk for, or protect them from, loneliness? After all, more freedom to choose whom to relate to may promote that individuals can choose higher-quality relationships (which protects from loneliness), but it may also imply a higher risk of social isolation (which puts at risk for loneliness). We propose that the solution to this cultural loneliness paradox of choice is to distinguish whether more individual choice flows fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…When compared to other parts of the world, these countries share a number of cultural elements (i.e., they contain some similar shared beliefs, norms, or values; Chiu, Gelfand, Yamagishi, Shteynberg, & Wan, 2010). For instance, they are generally characterized by higher individualism (Hofstede, Hofstede, & Minkov, 2010), lower relational stability (i.e., cultural norms to hold on to existing social relationships; Heu, Hansen, & van Zomeren, 2019), or less restrictive norms about social relationships (i.e., fewer, less strict, and less demanding norms about social relationships; Heu et al, 2020). As such, the cultures in these countries can be described as less socially embedded 2 : Individuals are less embedded in tight social networks (e.g., families or communities), spend more time or are more likely to live alone, have less stable and less long‐lasting relationships, and are more independent from each other when making choices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…When compared to other parts of the world, these countries share a number of cultural elements (i.e., they contain some similar shared beliefs, norms, or values; Chiu, Gelfand, Yamagishi, Shteynberg, & Wan, 2010). For instance, they are generally characterized by higher individualism (Hofstede, Hofstede, & Minkov, 2010), lower relational stability (i.e., cultural norms to hold on to existing social relationships; Heu, Hansen, & van Zomeren, 2019), or less restrictive norms about social relationships (i.e., fewer, less strict, and less demanding norms about social relationships; Heu et al, 2020). As such, the cultures in these countries can be described as less socially embedded 2 : Individuals are less embedded in tight social networks (e.g., families or communities), spend more time or are more likely to live alone, have less stable and less long‐lasting relationships, and are more independent from each other when making choices.…”
Section: Introductionmentioning
confidence: 99%
“… Notably, cultural characteristics can strongly vary within, as well as transcend, country borders. Individualism, relational stability (Heu, Hansen, & van Zomeren, 2019), restrictiveness (Heu et al, 2020), or social embeddedness should hence, on average , be higher or lower in a country, but levels can differ considerably between different cultural groups within that country (e.g., between more rural and more urban communities, communities with different political orientations, different age groups, or even different families). …”
mentioning
confidence: 99%
“…Are individuals more connected in their relationships in contexts that make relationships easier to move into and harder to move out of? Heu et al (2021) perhaps not surprisingly found that countries in which it was easier to start relationships featured lower levels of loneliness, but also found evidence (albeit less robust) that countries in which it was less permissible to leave relationships also featured lower loneliness. These data tentatively suggest the possibility that a progression bias may promote relationship connection.…”
Section: Future Directionsmentioning
confidence: 94%
“…Cross-cultural research may offer particular insight into this question, as different cultures vary in norms that allow for more versus less relational choice as well as norms that permit versus restrain the decision to leave established relationships ( Heu et al, 2021 ). Are individuals more connected in their relationships in contexts that make relationships easier to move into and harder to move out of?…”
Section: Future Directionsmentioning
confidence: 99%
“…We expected to observe the following patterns of resolution of the intimacy crisis: (a) successful resolution through persistent partnered status, (b) successful resolution indicated by the transition from single to partnered status, (c) unsuccessful resolution indicated by persistent single status, and (d) unsuccessful resolution indicated by the transition from partnered status to single status. Prior research on the role of sociocultural factors in the development and functioning in intimate relationships (Marshall, 2008) and loneliness (Heu et al, 2021; Rokach et al, 2004; Yum, 2003), suggests that national differences in the patterns of resolution of the intimacy crises among Polish and U.S. young adults may occur, although we did not formulate specific hypotheses for directions of these national patterns.…”
Section: Eriksonian Psychosocial Intimacy Versus Isolation Crisismentioning
confidence: 96%